Korelasi antara Religious Focus Coping dengan Burnout Akibat Covid-19 yang Dialami Orang Tua Kristen di Bandung Barat - Rudy Alouw; Ria Mei Sawitri; Slamet Triyadi; Saut Sihombing (SANCTUM DOMINE: JURNAL TEOLOGI, 2023)
Burnout is a serious threat to Christian parents due to Covid-19, because it can impact physical, emotional, and behavior that is not educating and assisting children effectively but can damage children's mentality. This study examines the relationship between religious focus coping and burnout in Christian parents in West Bandung. Data analysis using bivariate correlations technique with sampling technique using stratified random sampling. Because the population is unknown for certain, the minimum number of samples is 10 x the number of variables to determine the number of samples using the Roscoe formula. This study uses two variables, namely religious focus coping and burnout. Thus, the minimum number of samples should be 20. In this study, 43 Christian parents were involved, meaning that the specified number of samples met the requirements. The results showed that the correlation coefficient of religious focus coping with burnout was -0.495, which was strong enough. While the coefficient value marked - (negative) means that burnout is reduced or decreased due to high religious focus coping. The significance of the correlation was 0.001, smaller than the significance of alpha > 0.05. Because the significance of 0.001 is less than 0.05, hypothesis 0 (Ho) is rejected, while the alternative hypothesis (Ha) is accepted. This means a significant correlation or relationship exists between religious focus coping and burnout of Christian parents.